Design optimization of a pixel-based range telescope for proton computed tomography - Pettersen, Helge Egil Seime; Seco, Joao (Physica medica, 2019)
Purpose - A pixel-based range telescope for tracking particles during proton imaging is described. The detector applies a 3D matrix of stacked Monolithic Active Pixel Sensors with fast readout speeds. This study evaluates different design alternatives of the range telescope on basis of the protons’ range accuracy and the track reconstruction efficiency. - Method - Detector designs with different thicknesses of the energy-absorbing plates between each sensor layer are simulated using the GATE/Geant4 Monte Carlo software. Proton tracks traversing the detector layers are individually reconstructed, and a Bragg curve fitting procedure is applied for the calculation of each proton’s range. - Results - Simulations show that the setups with 4mm and thinner absorber layers of aluminum have a low range uncertainty compared to the physical range straggling, systematic errors below 0.3mm water equivalent thickness and a track reconstruction capability exceeding ten million protons per second. - Conclusions - In order to restrict the total number of layers and to yield the required tracking and range resolution properties, a design recommendation is reached where the proposed range telescope applies 3.5mm thick aluminum absorber slabs between each sensor layer.
Available online 06 June 2019
Gesehen am 23.10.2019